Investigating determinants of competitiveness of the retail banking service in Vietnam: a customer approach - Nguyen, Dac Thanh; Luu, Thi Thuy Duong; Nguyen, Huu That (Journal of International Economics and Management, 2022)
This study is conducted to clarify the impact of the factors on the competitiveness of retail banking services inVietnam’s commercial banks from the customer’s approach. The hypothesis in this paper is proposed that the competitiveness of retail banking services is related to the following factors: service quality, fees, distribution channels, promotion activities, and brand. The data is used from the survey conducted by 438 individual customers who have been using retail banking services in Vietnam’s big cities. This paper shows that the specific factors which are positively impact the competitiveness of retail banking services in Vietnam can be seen as prices (service fees), promotion activities, brand and distribution channels and service quality. The findings in this research could be an academic basis towards the improvement of the policies for retail banking services in Vietnam.